DEFINITION OF CONDITION СYTOPLASMATIC CELLULAR MEMBRANES WITH THE HELP OF METHODS BIOHEMILUMINESCENCE AND PHOSPHORESCENCE - Sirenko, E.V. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine")
Are experimentally determined increase of levels BHL, an intensification of a phosphorescence and increase of contents 2,4-dinitricphenilaldogidrasone and 2,4-dinitrophenilketogidrasone in biological liquids and tissue fabrics of bodies white rats which received subtoxik dozes of organic mixes on basis PEG during 45 day. The received data allow to assume ability of researched substances to lift density білково-липидного a layer cytoplasmatic membranes, to intensify free-radical processes, липидов and fibers to change structure and function of a cellular membrane which negatively influences a metabolism.